Analytická sonda – priestor pre tvorivosť? - Palgutová, Katarína (Univerzita Pardubice, 2014)
The method of analytical presentation (MAP) has become recently the object of a great discussion. Nowadays, its use is questionable, since one prefers the unity of a face heritage and one maximizes the effort to keeping an object’s substance. The MAP has a long tradition in our territory, where it is supported by the quality and methodologically completed realization. Any scholar has not devoted their work to the MAP globally neither from the methodological point of view nor the creative point of view. The goal of this thesis is to point out the fact that the high quality restoration together with presenting old developmental periods has a high documentary value. Naturally, it is necessary to také into account the fact that it is implemented on selected and stylistically heterogeneous objects while it is not used programmatically and area‐wide. The showpiece’s documentary value is a significant factor during the searching own roots, building the national identity in the current globalized world. The contribution acquaints with the created methodological system, which should be helpful for a mutual communication between an architect and a methodical worker. One of the goals of the author´s dissertation thesis was the creation of mentioned system. Needless to say that the creation of a rendering of an analytical probe could be the object of a creative process and it does not have to be its limit.
Analytic probe – area of creativity?
Keywords: method of analytic presentation; analytic probe; composition